Membangun Kewirausahaan Masyarakat Desa Pone Kecamatan Limboto Barat Kabupaten Gorontalo Berbasis Potensi Desa - LA ODE AMAN; Ahmad Kadir Kilo; Suleman Duengo (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2022)
KKN MBKM (Kuliah Karya Nyata Merdeka Belajar Kampus Merdeka) is a form of education that provides learning experiences for students to live in the community outside the campus and directly identify community potential and deal with problems so that they are expected to be able to develop the potential of villages and regions and gather solutions to problems that exist in the village. Real Work Lectures at this time coincide with the COVID-19 pandemic, so it has implications for governance differences with normal times. Various work programs have been planned before going to the KKN location, including the manufacture of hydroponic media and aquaponics, making hand sanitizer using natural materials, making Pone's food, and the implementation of tutoring to increase interest in learning from children who have been studying online for a long time. The results of this study show that community service program activities as a form of community service during the pandemic are still ongoing. The community can still feel the benefits, and the role of students can still be carried out with a series of innovative activities as well as continuing to follow health protocols.